Coastal Adolescents' Perceptions of Higher Education: Persepsi Remaja Pesisir Pantai Tentang Pendidikan di Perguruan Tinggi - Marwansyah, Marwansyah; Ritonga, Hasnun Jauhari (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Education is a cornerstone for the development of high-quality human resources. Specific Background: In remote coastal areas, access and motivation toward higher education remain limited. Knowledge Gap: Limited research explores how adolescents in such marginalized regions perceive higher education and the factors that hinder their participation. Aim: This study investigates the perceptions of coastal adolescents in Dahari Selebar Village regarding higher education and the sociocultural factors influencing their educational decisions. Methodology: Using a qualitative approach, data were collected through observations and in-depth interviews with five adolescents who discontinued their formal education and the village head. Results: Findings reveal that although adolescents perceive higher education positively—associating it with self-development, future success, and achieving aspirations—socioeconomic constraints, insufficient parental encouragement, and entrenched local norms often discourage educational continuation. Novelty: This study provides an in-depth account of educational aspirations in coastal youth, highlighting a tension between positive perception and structural barriers. Implications: The findings underscore the urgency of targeted interventions to raise awareness and provide socioeconomic support in coastal regions, contributing to efforts aimed at enhancing educational equity and preparing future generations to navigate global challenges. Highlights: Highlights coastal adolescents' positive yet conflicted view on higher education. Reveals economic and parental factors as key obstacles to continuation. Urges targeted support and awareness to improve educational access. Keywords: Adolescent Perception, Higher Education, Coastal Communities, Educational Barriers